Ground-truthing social vulnerability indices of Alaska fishing communities. Issue 5 (3rd September 2018) - Lavoie, Anna; Sparks, Kim; Kasperski, Stephen; Himes-Cornell, Amber; Hoelting, Kristin; Maguire, Conor
Abstract: Community vulnerability is increasingly evaluated through quantitative social indices, typically developed using secondary data sources rather than primary data collection. It is necessary to understand the validity of these indices if they will be used to inform policy and decision making. This paper presents a ground-truthing effort to validate quantitative indices that characterize the well-being of Alaska fishing communities. We utilized ethnographic data collected from 13 representative communities and a capital assets framework to ground-truth the indices, in which qualitative ranks of vulnerability were compared against quantitative indices. The majority (73.8%) of ranks were in complete or moderate agreement and the results indicate that most of the indices are representative of community vulnerability; yet some variables utilized to create the indices could be modified to better reflect realities in Alaska. Indices of commercial fishery engagement and reliance appeared to be more reliable than socio-economic indicators, particularly for smaller fishing communities. We also confirmed that the indices do not capture political, or ecological factors that affect levels of community vulnerability. We conclude that quantitative indices of community vulnerability are useful rapid assessment tools; however, they should be validated, and complemented with ethnographic data prior to their implementation as policy making and management tools.